Contextualization and conceptualization of the determinants of self-initiated expatriates’ international opportunity recognition in an informal economy context - Ramsey, Jase R.; Posthuma, Richard A.; Abi Aad, Amine; Maalouf, Jamal (Journal of comparative international management, 2025)
This study introduces an updated conceptual model that extends the contextual literature on self-initiated expatriates (SIEs) into the opportunity recognition framework. Integrating individual and contextual factors, this model examines opportunity recognition by SIEs in informal economies, an under-researched area. The current global migration context, characterized by economic opportunities, geopolitical conflicts, and environmental changes, is leading to significant demographic and labor transformations. These changes are having a substantial impact on international entrepreneurship. The new model extends experiential learning and self-construal theories, incorporating work experience in informal economies, cultural intelligence, individualism, and risk aversion. This model illustrates how SIEs leverage their diaspora connections and advanced cross-cultural competencies to navigate and utilize the entrepreneurial ecosystem effectively. Additionally, the study provides new and testable research propositions. This approach offers a comprehensive understanding of how SIEs recognize and pursue opportunities in informal economies, highlighting the intricate interplay between individual attributes and contextual influences.